Plan estratégico para la empresa comintegra ubicada en la ciudad de Ibarra, en el periodo 2013-2015 - Macías Macías, Eugenia Mariela (2013)
This research was conducted with the purpose of improving the activities in COMINTEGRA Company, through the implementation of a strategic plan, properly structured based on the problems and anomalies in the development of the plan. This work contains criteria and basic planning concepts linked to the proper administration, summarized the elements that must contain a strategic plan, reviewing relevant aspects that must be considered for proper planning, which is proposed for projects whose activities should be carried on schedule to achieve the expected results within the stipulated time. Data collection was done through the use of surveys to consumers of organic products, made up of 13 questions, along with the use of the method of observation, the results it was found that there are limitations in the planning of the company, in finding that 72% said that the company has poor planning. Were designed and applied the techniques and methods that once analyzed, contributed to the testing of the hypothesis, later issuing the respective conclusions and recommendations based on the study.